Design of Student Campuses and its Ecological Properties - Ibragimovna, Sobirova Ozoda (European Journal of Life Safety and Stability (2660-9630), 2022)
The article aims to consider the stages of the ecological properties and formation of such a device for organizing the life of students as a dormitory or a campus. The method of conducting a comparative analysis between Uzbekistan and foreign analogues reveals common and regular features. As a result, it is possible to identify individual signs of the most successful design solutions and draw conclusions about the feasibility of applying them directly in our current situation.